Tax Evasion from Cross-Border Fraud : Does Digitalization Make a Difference? - Kitsios, Emmanouil (IMF Working Papers; Working Paper ;, 2020)
How can governments reduce the prevalence of cross-border tax fraud? This paper argues that the use of digital technologies offers an opportunity to reduce fraud and increase government revenue. Using data on intra-EU and world trade transactions, we present evidence that (i) cross-border trade tax fraud is non-trivial and prevalent in many countries; (ii) such fraud can be alleviated by the use of digital technologies at the border; and (iii) potential revenue gains of digitalization from reducing trade fraud could be substantial. Halving the distance to the digitalization frontier could raise revenues by over 1.5 percent of GDP in low-income developing countries.